Biological phosphorus removal in wastewater treatment plants - Ozdemir, Burcu (My University, 2004)
BIOLOGICAL PHOSPHORUS REMOVAL IN WASTEWATER TREATMENT PLANTS Phosphorus is an essential part of the nutrient cycle in nature for all life forms. Biological nutrient removal (BNR) is commonly the most economical means of removing nitrogen and phosphorus from wastewaters to control eutrophication in lakes and water bodies, and to prevent the deterioration of water quality. There is an increasing trend for water quality legislation to require the removal of phosphorus from wastewater. Furthermore, the recovery of phosphorus is an increasing subject of deal as phosphorus is a non-renewable natural resource which is exhausting by modern society. Phosphorus removal in Pasakoy Wastewater Treatment Plant is modelled by a parametric model developed by South African researchers Ekama and Marais (of Cape Town University). The model is calibrated using full scale operational data of Pasakoy Wastewater Treatment Plant (R2 = 0,73). The average influent readily biodegradable COD concentration in the plant varies between 7-70 and the average value of dry weather conditions is 40 mg/ L. Hence, return sludge nitrates effect the bio-P process. The on line measured oxidation reduction potentials of the anaerobic tanks and the first anoxic tank are between -50/ -100 mV and -200/ -300 mV respectively. A pilot scale anaerobic lagoon was used as a side stream fermenter and P-stripper to study the feasibility of making fertilisers by reacting the phosphates stripped from the waste sludge by commercial powdered slaked lime. The average readily biodegradable COD and total phosphorus concentration of the supernatant from the lagoon was 150 mg/ L and 41 mg/ L respectively. Approximately, fertiliser containing 15 kg of P was produced per day by reacting the anaerobic lagoon supernatant with slaked lime in the pilot plant and 0.31 kg of P was produced per kg of lime consumed. The P content in the fertiliser sludge was %4. July, 2004 Burcu Ozdemir

ATIKSU ARITMA TESİSLERİNDE BİYOLOJİK FOSFOR GİDERİMİ Fosfor tüm canlılar için doğadaki besin döngüsünün önemli bir parçasıdır. Biyolojik nutrient giderimi, göller ve yüzeysel su kaynaklarında ötrofikasyonun kontrol altına alınması ve su kalitesinin korunması için atıksulardan azot ve fosfor gideriminde en yaygın ve ekonomik yöntemdir. Fosforun atıksudan arıtılması gün geçtikçe daha bağlayıcı olmaktadır. Ayrıca fosfor kaynakları sürekli tüketilen ve yenilenemeyen bir element olduğundan, fosforun geri kazanımı giderek önem kazanan bir konudur. Paşaköy Atıksu Arıtma Tesisi'nde fosfor giderimi Ekama ve Marais(Cape Town Üniversitesi) tarafından geliştirilen modelle kütle dengesine bağlı olarak modellenmiştir ve Paşaköy Atıksu Arıtma Tesisi değerlerine bağlı olarak kalibre edilmiştir (R2 = 0,73). Giriş atıksuyunda kolay ayrışabilen KOİ 7-70 mg/ L arasında değişmektedir ve kuru havada ortalama 40 mg/ L olmaktadır. Bu nedenle fosfor giderimi geri devir nitrat konsantrasyonundan birinci derecede etkilenmektedir. Tesiste otomasyonla sürekli izlenen redoks potansiyelleri anaerobic ve anoxic tanklarda sırasıyla -50 / -100 ve -200 / -300 arasında değişmektedir. Ayrıca atık çamurdan ticari sönmüş toz kireç ile kalsiyum fosfatlı gübre üretimi için bir pilot çalışma yapılmıştır. Fosfor salınımı gerçekleştirmek için anaerobik lagün fermenter olarak kullanılmıştır. Lagün üst suyunda kolay ayrışabilir KOİ ve P değerleri sırasıyla ortalama 150 ve 41 mg/ L bulunmuştur. Günlük yaklaşık 15 kg P ve harcanan kg kireç başına yaklaşık 0,31 kg P üretilmiştir. Üretilen gübre, % 4 P içermektedir. Temmuz, 2004 Burcu Özdemir
Keywords: Biyoloji